Hepatitis B serologic patterns in children of HBV carriers or infected mothers - Julfina Bisanto; Imral Chair; Dyah Istikowati (Paediatrica Indonesiana, 2004)
Background Vertical transmission is usually the cause of increas-ing carrier rates for hepatitis B infection, especially in highly en-demic areas.Objective To determine the serologic patterns of hepatitis B inchildren of HBV carrier/infected mothers.Methods This was a cross sectional study on children of HBVcarrier/infected mothers. Subjects were recruited consecutively andexamined at the Department of Child Health, Cipto MangunkusumoHospital during January–July 2003. Children were included if theywere generally healthy and their parents gave permission. Chil-dren with chronic illness, previous blood transfusions, or drug abusewere excluded.Results Fifty-nine children of 32 HBV carrier/infected mothers wererecruited. HBsAg was positive in 8 children, anti-HBs in 37, andanti-HBc in 4 children. Seventy-three percent of children had beenvaccinated against HBV but only 81% had positive anti-HBs. Ofeighteen children who received hepatitis B vaccine and HBIg atbirth, none was infected. Six out of 25 children who received onlyhepatitis B vaccine were infected.Conclusion HBsAg, anti-HBs, and anti-HBc were positive in 14%,36%, and 7% of children of HBV carrier/infected mothers, respec-tively